A review of public and environmental consequences of organic germanium. Issue 13 (2nd July 2020) - Zheng, Jiangfu; Yang, Lihua; Deng, Yaocheng; Zhang, Chenyu; Zhang, Yang; Xiong, Sheng; Ding, Chunxia; Zhao, Jia; Liao, Chanjuan; Gong, Daoxin
Abstract: Germanium (Ge) is a widely distributed but rare element on earth. Organic germanium is the most widely used form of germanium. Compared to the common metal (mercury, cadmium, lead, etc.), organic germanium is much less toxic to humans than others. Since its discovery in 1886, organic germanium and relative compounds have caused many medically related problems across the globe. In most cases, organic germanium exists in the natural environment in an oxidation state. The size of organic germanium and its compounds is extremely small in natural water, for which organic germanium can easily enter the environment through the flow of water. Because organic germanium owns unique chemical properties and is potentially ecotoxic, so there are have special environmental problems. Considering the fact that people does not know much about organic germanium, along with the lack of systematic research, this paper starts with a brief introduction of the chemical composition, distribution, and threat to human health of organic germanium. Then, the new and common technologies for the recovery and removal of germanium as referred to in various literatures introduced and with detail description of their performance, advantages, disadvantages, and applications. It is of great significance for people to understand organic germanium and its pollution control. Graphical Abstract: